PENINGKATAN HASIL BELAJAR KOGNITIF SISWA DENGAN MENERAPKAN MODEL KOOPERATIF TGT BERBANTUAN MEDIA MONOPOLI PADA MATERI SISTEM TATA SURYA - Agustin, Zulfani Nurdiana; Budiyanto, Mohammad; Qosyim, Ahmad (Universitas Negeri Surabaya, 2024)
This study aims to describe the improvement of cognitive learning outcomes and students' responses to the application of the monopoly media-assisted TGT cooperative model on solar system materials. The research method used is pre-experimental design with one group pretest and posttest design. This research was conducted at Pamekasan City Junior High School, with 30 research subjects. The data collection technique uses the test method and response questionnaire, with the instruments used being test question sheets and student response questionnaires. The analysis techniques used are N-Gain analysis for improving students' cognitive learning outcomes and quantitative descriptive analysis for student responses. The results of the study show that the TGT cooperative model assisted by monopoly media can improve students' cognitive learning outcomes, as evidenced by the overall average N-Gain score of 0.73 in the high category, and get an average very positive response from students with a percentage of 83%.